Diversify first! Fatten the tails of phenotypic diversity to enhance adaptive capacity in the Anthropocene - Charles H. Cannon; Chai-Shian Kua (Global Ecology and Conservation, 2025)
The current pace of environmental change exceeds what most organisms have experienced over the past few million years, with more extreme shifts and events anticipated in the Anthropocene. Emerging environments will include novel combinations of abiotic and biotic conditions, forcing populations and species to either adapt or migrate to avoid extinction. Endogenous mutation rates are slow, particularly as natural populations decline and fragment. Phenotypic plasticity has its limits, particularly at extremes of physiological tolerance. Migration is only effective if appropriate habitat exists within dispersal abilities. Introgressive hybridization, an important element of natural diversification, has been effective means to generate novel vigorous phenotypes. Assisting phenotypic diversification through introgressive hybridization among suites of partially interfertile species could be an effective conservation strategy to enable endangered species to adapt and respond. These suites of species function as a geographically and taxonomically networked syngameon, allowing exchange of advantageous traits, replenishing genetic diversity, and restoring lost ecological and physiological functions. Phenotypic outliers within species - individuals with rare but beneficial traits - are important for maintaining adaptive potential within these networks. Fortunately, species typically maintain their cohesive identities given natural levels of interspecific genetic exchange. Experimental programs and theoretical studies will be essential to explore the impacts of accelerated introgressive hybridization within defined syngameons, with the goals of addressing uncertainties and refining methods. As environmental changes accelerate, promoting phenotypic diversification through hybridization offers a proactive strategy to maintain adaptive capacity. This approach has the potential to safeguard biodiversity and ecosystem functionality through the upcoming biodiversity bottleneck.